The Mediating Role of Employee Engagement in the Influence of Performance and Workload on Employee Retention: A Study of Boarding Schools - Rahmat Wiyoga; Nugraha Saefudin (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2026)
The phenomenon of rising turnover amid high performance achievement represents an anomaly that calls for psychological explanation. This study aims to examine the mediating role of employee engagement in the relationship between employee performance and workload on employee retention in a boarding school setting. The research population consisted of 228 employees at Sekolah Islam Nurul Fikri Boarding School Serang, with a sample of 146 respondents selected through proportional random sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that employee performance has a positive effect on employee engagement (β = 0.676, t = 11.781) but no direct effect on retention (β = 0.040, t = 0.363). Workload has no significant effect on employee engagement (β = -0.011, t = 0.123) yet exerts a negative effect on retention (β = -0.255, t = 3.994). Employee engagement fully mediates the influence of performance on retention (β = 0.445, t = 7.670), whereas its mediating role in the workload–retention link is not significant. These findings confirm that retention is not directly influenced by performance; rather, the effect is transmitted through employee engagement. In contrast, workload directly reduces retention without operating through the engagement mechanism. The integration of AMO theory, the JD-R model, and Social Exchange Theory successfully elucidates these dynamics, particularly within the high-demand context of boarding school education. The managerial implications underscore the need for employee engagement enhancement programs and structural workload management.